PERAN AYAH DALAM PERSPEKTIF ISLAM DAN IMPLEMENTASINYA TERHADAP SISWA MADRASAH ALIYAH NEGERI (MAN) DI JAKARTA - Bunyanul Arifin (Universitas Muhammadiyah Tangerang, 2019)
Father's role in children is very important. The child's success is determined by the way the father treats his child. The purpose of this study is to empirically analyze the concepts of fathers and their role in children in an Islamic perspective and measure the level of implementation in the field. Type of descriptive qualitative research with respondents of 500 MAN students in West Jakarta. Data obtained through; observation, questionnaire, and interview. Also from written documents, drawings and literature studies. In this study the author formulates the role of the father into six dimensions, namely the role as; 1) leaders, 2) providers of economic needs, 3) protectors, 4) educators, 5) playmates, 6) friends. The study concluded that father's role in children in Islamic perspective was 44 (%). The highest role as a protector 64 (%), then the economic provider 60.8 (%). The lowest role as a friend is 25.3 (%), then a friend plays 29 (%). Leader's role is 44.7 (%), and as an educator 40.8 (%). The conclusion of the study is that the implementation of the role of fathers in an Islamic perspective is relatively small, and needs further research on their influence on children.